KONSEP ISLAM DAN IMAN Analisis Pemikiran Inklusivisme Muhammad Shahru>r - Laila Rohani (Jurnal Theologia, 2012)
The basic question being answered in this paper is how to construct inclusiveness thinking of Muhammad Shahrur about Islam and Iman (faith) he explores from the Quran? And what are the implications of such thinking. From his depth studies of the Quran, Shahrur believes that salvation doesn't only belong to one religion or the salvation of Muslims alone but it can also be found in a religion other than Islam. Anyone who surrenders to God believes in the Day of Judgment and doing a good deed, according to Shahrur, referred to as Muslims. It does not distinguish who he was and comes from what kind of formal religion. That is the conclusion found from his thoughts about religious attitudes. Pertanyaan mendasar yang hendak dijawab dalam tulisan ini adalah bagaimana konstruk pemikiran inklusivisme Muh}ammad Shah}rur tentang Islam dan iman yang dieksplorasinya dari al-Quran? Dan  apa implikasi dari pemikirannya tersebut. Dari kajianya yang mendalam terhadap al-Quran, Shah}rur berkeyakinan bahwa keselamatan tidak hanya milik satu agama atau orang Islam saja tetapi keselamatan itu bisa pula ditemukan di dalam agama selain Islam. Siapa  saja yang pasrah kepada Tuhan beriman kepada hari akhir, dan beramal saleh, menurut Shah}rur, disebut sebagai seorang Muslim. Ia tidak membedakan siapa orang itu dan berasal dari agama formal apa, demikian kesimpulan yang ditemukan dari buah pikirannya tentang sikap keberagamaan.